Pengaruh Pengetahuan Investasi dan Kemajuan Teknologi Terhadap Keputusan Investasi Dengan Minat Investasi Sebagai Variabel Intervening: Studi Pada Mahasiswa Program Studi Manajemen Universitas Negeri Makassar - Sahabuddin, Romansyah; Arif, Hery Maulana; Zakira, Nur Amni; Aulia, Insyirach; Efendy, Arifai Sosila (Journal Management & Economics Review (JUMPER), 2024)
With investment interest as an intervening variable, this study seeks to examine how investment knowledge and progress impact investment decisions, especially for Makassar State University students enrolled in the Management Study Program. Investment is a financial commitment made with the hope of gaining profits in the future. Although technological advances have facilitated access to various digital platform investment instruments, having adequate investment expertise is still needed to prevent losses. Knowledge and technological advances impact investment interest, which measures a person's interest in carrying out investment activities. This study uses a quantitative approach using the SmartPLS 3.38 application to analyze structural equality modeling (SEM). The study population was 530 students, whose samples were taken randomly. The findings of the analysis indicate that technological advances and investment knowledge have a significant impact on investment interest, which in turn influences students' investment choices. These results highlight the importance of improving the interest and financial literacy of the younger generation in order to facilitate better investment decision-making. It is hoped that this study will offer suggestions for creating university-level financial education initiatives.